FEATURES OF VISUAL REPRESENTATION OF THE FUTURE OF RUSSIA: METHODOLOGICAL ASPECTS OF THE STUDY - Inga Vladislavovna Zheltikova (Sovremennye Issledovaniâ Socialʹnyh Problem, 2019)
Purpose. The purpose of the paper is to determine the methodology of studying the images of the future of contemporary Russia.